An overview of blockchain research and future agenda: Insights from structural topic modeling - Anuja Shukla; Poornima Jirli; Anubhav Mishra; Alok Kumar Singh (Journal of Innovation & Knowledge (JIK), 2024)
As a disruptive technology, blockchain has become a strategic priority for many businesses. A vast amount of research exists on blockchain's innovative nature and immense potential for multiple industries. This study aims to synthesize the existing research to classify the findings into various themes and propose avenues for further research. A total of 2,360 academic articles were analyzed using the text-mining method of structural topic modeling. The identified fifteen topics were mapped to the four quadrants of the Datatopia model, leading to the development of the Datatopia-blockchain (DBlock) framework. The results present future scenarios that provide an understanding of what is known about blockchain, its characteristics, and potential research areas. The contributions to the theory and implications to the practitioners are discussed in detail.
Keywords: O32; O33; 650; Structural topic modeling; Blockchain; Scenario building; Datatopia; Natural language processing; Emerging technologies